2001
DOI: 10.1200/jco.2001.19.9.2509
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Docetaxel, Estramustine, and Low-Dose Hydrocortisone in Men With Hormone-Refractory Prostate Cancer: A Final Report of CALGB 9780

Abstract: This therapy is efficacious and moderately well tolerated in HRPC and should be compared in a phase III trial with mitoxantrone and prednisone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
178
2
8

Year Published

2002
2002
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(203 citation statements)
references
References 19 publications
15
178
2
8
Order By: Relevance
“…The median duration of the palliative response was about 10 months, which is similar to that recently observed with the use of mitoxantrone + prednisone or taxotere, and longer than that found with prednisone alone, vinorelbine or paclitaxel (Tannock et al, 1996;Fields-Jones et al, 1999;Trivedi et al, 2000;Savarese et al, 2001). The palliative response was accompanied by an improvement in a number of the quality of life dimensions, particularly a reduction in pain and an improvement in functional scales.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The median duration of the palliative response was about 10 months, which is similar to that recently observed with the use of mitoxantrone + prednisone or taxotere, and longer than that found with prednisone alone, vinorelbine or paclitaxel (Tannock et al, 1996;Fields-Jones et al, 1999;Trivedi et al, 2000;Savarese et al, 2001). The palliative response was accompanied by an improvement in a number of the quality of life dimensions, particularly a reduction in pain and an improvement in functional scales.…”
Section: Discussionsupporting
confidence: 84%
“…Most previous studies have found little evidence of anti-tumour activity, with response rates of less than 10% for single chemotherapeutic agents and similar results for combination therapies (Eisenberger et al, 1985;Millikan, 1999). However, more recent studies with mitoxantrone, docetaxel and estramustine have shown a response (Tannock et al, 1996;Savarese et al, 2001). It is difficult to assess the effectiveness of chemotherapeutic agents in the treatment of metastatic prostate cancer because the patients often do not have measurable disease (Coleman, 1998).…”
mentioning
confidence: 99%
“…After palliative responses were seen in two randomized studies that involved mitoxantrone and corticosteroid, this became the only FDA-approved chemotherapeutic combination for metastatic prostate cancer 67,68 . Other combination therapies have included agents such as estramustine, vincristine, etoposide, doxorubicin, and the taxanes paclitaxel and docetaxel [69][70][71][72][73] . Emerging clinical data indicate a survival advantage in patients treated with these newer chemotherapy combinations who have a significant fall (that is, >50-75%) in serum PSA 74 .…”
Section: Cytotoxic Chemotherapymentioning
confidence: 99%
“…In fact, besides vinorelbine, 22,23 several studies have combined a taxane with estramustine with encouraging results in terms of response rate and survival. [24][25][26][27] However, significant toxicity was again observed in all of these studies. The thrombotic complications have been a source of concern for many investigators and have resulted in prophylactic regimens being introduced into the trials, with the aim of mitigating this toxicity.…”
Section: Discussionmentioning
confidence: 85%